Genomic Sequence Analysis for Exon Prediction Using Adaptive Signal Processing Algorithms - Rahman, Md. Zia Ur (Muhammad Zia Ur), author 650115; Putluri, Srinivasareddy, author 650116 (Boca Raton : CRC Press, 2021)
"This book addresses the issue of improving the accuracy in exon prediction in DNA sequences using various adaptive techniques based on different performance measures which is crucial in disease diagnosis and therapy. Six chapters are presented"--